EFEKTIVITAS YOGA DALAM MENGATASI KECEMASAN DAN DEPRESI KEHAMILAN : A SCOPING REVIEW - Sarmin, Sukati; Makiyah, Sri Nabawiyati Nurul; Fatmawati, Elis (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Psychological disorders can occur during pregnancy and become serious health problems, such as depression and anxiety. Anxiety that occurs simultaneously with depression during pregnancy has a negative impact on the mother and baby. Practicing yoga while pregnant is beneficial as a health improvement and has therapeutic effects on illness, depression, stress and anxiety. This review aims to determine the effectiveness of yoga in treating anxiety and depression during pregnancy. This research method uses the scoping review method with the Arksey and O'Malley framework. Systematic review through PubMed, Willey, ProQuest and Gray Literature databases using predetermined keywords. It was found that 11 of the 562 articles were selected based on inclusion and exclusion criteria. The effectiveness of yoga is described in three themes, namely the effectiveness of yoga in overcoming anxiety, depression and yoga safety. The conclusion of this review states that yoga is effective in reducing depression and anxiety in pregnant women with or without depression.